Effects of global change drivers on the expression of pathogenicity and stress genes in dryland soil fungi - Adriana L. Romero-Olivares; Andrea Lopez; Jovani Catalan-Dibene; Scott Ferrenberg; Samuel E. Jordan; Brooke Osborne (mSphere)
ABSTRACT The impacts of global climate change on dryland fungi have been understudied even though fungi are extremely sensitive to changes in the environment. Considering that many fungi are pathogens of plants and animals, including humans, their responses to anthropogenic change could have important implications for public health and food security. In this study, we investigated the potential physiological responses (i.e., metatranscriptomics) of pathogenicity and stress in dryland fungi exposed to global change drivers, drought, and the physical disturbance associated with land use. Specifically, we wanted to assess if there was an increase in the transcription of genes associated to pathogenicity and stress in response to global change drivers. In addition, we wanted to investigate which pathogenicity and stress genes were consistently differentially expressed under the different global change conditions across the heterogeneous landscape (i.e., microsite) of the Chihuahuan desert. We observed increased transcription of pathogenicity and stress genes, with specific genes being most upregulated in response to global change drivers. Additionally, climatic conditions linked to different microsites, such as those found under patches of vegetation, may play a significant role. We provide evidence supporting the idea that environmental stress caused by global change could contribute to an increase of pathogenicity as global climate changes. Specifically, increases in the transcription of stress and virulence genes, coupled with variations in gene expression, could lead to the onset of pathogenicity. Our work underscores the importance of studying dryland fungi exposed to global climate change and increases in existing fungal pathogens, as well as the emergence of new fungal pathogens, and consequences to public health and food security.IMPORTANCEThe effects of global climate change on dryland fungi and consequences to our society have been understudied despite evidence showing that pathogenic fungi increase in abundance under global climate change. Moreover, there is a growing concern that global climate change will contribute to the emergence of new fungal pathogens. Yet, we do not understand what mechanisms might be driving this increase in virulence and the onset of pathogenicity. In this study, we investigate how fungi respond to global change drivers, physical disturbance, and drought, in a dryland ecosystem in terms of pathogenicity and stress. We find that indeed, under global change drivers, there is an increase in the transcription and expression of genes associated to pathogenicity and stress, but that microclimatic conditions matter. Our study shows the importance of investigating dryland fungi exposed to global climate change and impacts on our society, which may include threats to public health and food security.